1987
DOI: 10.1055/s-2007-1011727
|View full text |Cite
|
Sign up to set email alerts
|

Lipoproteins Status in Professional Football Players After Period of Vacation and One Month After a New Intensive Training Program

Abstract: Plasmatic lipoproteins were evaluated in a group of 11 professional football-players after a 3-week rest, and one month later, after an intensive training (characterized by a succession of aerobic and anaerobic efforts), for engaging a new competition. At day 0, total cholesterol (TC = 4.4 +/- .04 mmol/l), triglycerides (TG = .6 +/- .04 mmol/l), and LDL-TC (2.54 +/- .18 mmol/l) were significantly decreased versus sex and age matched sedentary subjects (TC = 5.13 +/- .2 mmol/l, P less than .02; TG = .99 +/- . m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Some studies showed that physical training has no significant effect on the lipid profile. 16 – 18 , 35 Kishali et al, 13 in a study involving subjects with different levels of physical training (20 male elite athletes, 44 trained men and 51 trained women, and 51 sedentary women) found no significant difference in plasma lipids between these groups. These authors reported that HDL cholesterol was higher in females than in sedentary and trained males, and that LDL cholesterol was lower in females (both sedentary and trained) than in males.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that physical training has no significant effect on the lipid profile. 16 – 18 , 35 Kishali et al, 13 in a study involving subjects with different levels of physical training (20 male elite athletes, 44 trained men and 51 trained women, and 51 sedentary women) found no significant difference in plasma lipids between these groups. These authors reported that HDL cholesterol was higher in females than in sedentary and trained males, and that LDL cholesterol was lower in females (both sedentary and trained) than in males.…”
Section: Discussionmentioning
confidence: 99%
“…Part of the rationale for LpL being an important factor in lowering postprandial TG is that they follow a similar time course of action [10,11]. However, it seems that when TG remains stable, LpL activity may not be modified [30].…”
Section: Discussionmentioning
confidence: 99%
“…The range of adaptations depends on the type, frequency, intensity, and duration of exercise [10][11][12]. Athletes have higher HDL-C, lower TG, and lower total cholesterol (TC) and LDL-C than sedentary individuals [12][13][14][15][16][17]. There are also reports that did not confirm that the lipid profile of athletes differed significantly from non-athletes [18,19].…”
Section: Introductionmentioning
confidence: 99%